2005
DOI: 10.1111/j.1471-4159.2005.03062.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrin signaling cascades are operational in adult hippocampal synapses and modulate NMDA receptor physiology

Abstract: Integrin class adhesion proteins are concentrated at adult brain synapses. Whether synaptic integrins engage kinase signaling cascades has not been determined, but is a question of importance to ideas about integrin involvement in functional synaptic plasticity. Accordingly, synaptoneurosomes from adult rat brain were used to test if matrix ligands activate integrin-associated tyrosine kinases, and if integrin signaling targets include NMDA-class glutamate neurotransmitter receptors. The integrin ligand peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(112 citation statements)
references
References 104 publications
(261 reference statements)
5
107
0
Order By: Relevance
“…This is not wholly unexpected because cytoskeletal regulation is a primary function of integrins across all types of cells (Zhu and Assoian, 1995;Geiger et al, 2002;DeMali et al, 2003) and there is compelling evidence that ß1 integrins regulate synaptic kinase signaling, the activities of synaptic NMDA receptors (Bernard-Trifilo et al, 2005), and processes critical for the stabilization of LTP (Chun et al, 2001;Kramár et al, 2002Kramár et al, , 2006Chan et al, 2003Chan et al, , 2006Kramár and Lynch, 2003). Nevertheless, the new results obtained with the F-actin labeling method provide the first evidence that theta bursts engage the integrin-actin system in the adult nervous system.…”
Section: Expressionmentioning
confidence: 99%
“…This is not wholly unexpected because cytoskeletal regulation is a primary function of integrins across all types of cells (Zhu and Assoian, 1995;Geiger et al, 2002;DeMali et al, 2003) and there is compelling evidence that ß1 integrins regulate synaptic kinase signaling, the activities of synaptic NMDA receptors (Bernard-Trifilo et al, 2005), and processes critical for the stabilization of LTP (Chun et al, 2001;Kramár et al, 2002Kramár et al, , 2006Chan et al, 2003Chan et al, , 2006Kramár and Lynch, 2003). Nevertheless, the new results obtained with the F-actin labeling method provide the first evidence that theta bursts engage the integrin-actin system in the adult nervous system.…”
Section: Expressionmentioning
confidence: 99%
“…These subunits define the two major families of integrins expressed in brain (Milner and Campbell, 2002); ß1-containing integrins are of particular interest because they modulate glutamatergic synaptic transmission Bernard-Trifilo et al, 2005) and plasticity (Kramár et al, 2002;Chan et al, 2003;Chan et al, 2006;Huang et al, 2006;Kramár et al, 2006). The effects of the integrin ligands and antisera on perikaryal [Ca 2+ ]i as assessed over time and at the initial peak RGD-induced increase for three experimental sets are summarized in figure 2.…”
Section: Integrin Ligands Increase [Ca 2+ ]I In Cortical Neuronsmentioning
confidence: 99%
“…Integrin ligand induced increases in [Ca 2+ ]i are blocked by the broad spectrum tyrosine kinase inhibitor genistein (Xie et al, 1998;Schottelndreier et al, 1999;Wu et al, 2001) as well as by the Src family kinase inhibitor PP2 (Schottelndreier et al, 2001;Wu et al, 2001) in non-neural cells. Other work has shown that integrin signaling activates kinases (CamKII, Src, MAPK p42/44) that modulate glutamate neurotransmitter receptor and VSCC function in neurons Bernard-Trifilo et al, 2005;Watson et al, 2007) and receptor tyrosine kinases in other systems (Miranti and Brugge, 2002). Moreover, there is evidence that CamKII-mediated phosphorylation of ryanodine receptors potentiates calciuminduced release from intracellular stores (Zhang et al, 2004).…”
Section: Increased Calcium Content Is Blocked By Genisteinmentioning
confidence: 99%
See 2 more Smart Citations